Determinants of preeclampsia in pregnant women - Neni Rahma Agustin; Marlina Marlina; I Gusti Ayu Mirah Widhi Sastri; Adinda Juwita Sari (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Preeclampsia is a serious pregnancy complication and a major contributor to maternal and fetal morbidity and mortality worldwide, including in Indonesia. This condition is generally characterized by hypertension that appears after >20 weeks of gestation, accompanied by proteinuria, and can progress to eclampsia if not treated appropriately. Purpose: to determine the relationship between age, parity, gestational age, and occupation with the incidence of preeclampsia in pregnant women. Method: Study quantitative with a cross-sectional design. The sample consisted of 58 pregnant women with preeclampsia and was selected using a total sampling technique. Bivariate analysis was performed using the chi-square test and odds ratio (OR). Results: The results showed a significant relationship between age (p = 0.002; OR = 6.222), parity (p = 0.002; OR = 6.182), and gestational age (p = 0.003; OR = 7.104) with the incidence of preeclampsia. Meanwhile, there was no significant association between occupation and the incidence of preeclampsia (p = 0.227; OR = 0.577). conclusion: there is a significant association between age, parity, and gestational age with the incidence of preeclampsia. It is hoped that health workers can improve early detection and more intensive monitoring of high-risk pregnant women based on age, parity, and gestational age to prevent the progression of preeclampsia to more severe conditions.